Analisis Putusan No : 397/PID. SUS/2019/PN.MTR terkait Penerapan Pidana terhadap Pelaku Tindak Pidana Narkotika Golongan I - Sariful Islam; Ufran Ufran (Indonesia Berdaya, 2023)
This research purpose to examine the judge's considerations in deciding cases of narcotics group I (verdict No.397/Pid.Sus/2019/PN.Mtr) and the criminal application of narcotics dealers in class I (verdict No.397/Pid.Sus/2019/PN.Mtr). The method using is normative legal research, with the statute approach, conceptual, and cases. The results of the research show First: Judge's consideration in imposing a crime based on judicial considerations which includes facts revealed in the trial process conclusion based on the testimony of the defendant, witnesses, and evidence. also covering that alleviate and incriminate the defendant. Second: The criminal application against criminal act without the rights to possess narcotics class I, not a plant, in cases No.397/Pid.Sus/2019/PN.Mtr. the prosecutor used alternative charges: primair Article 114 Paragraph (1) and subsidiair Article 112 Paragraph (1) of the Narcotics Acts.